Elevated Circulating Tissue Factor Procoagulant Activity, Factor VII, and Plasminogen Activator Inhibitor-1 in Childhood Obesity: Evidence of a Procoagulant State - Singh, Anamika (2012)
Childhood obesity is rapidly increasing in prevalence. We compared circulating membrane-bound tissue factor (FIII, F3) procoagulant activity (TF-PCA) and plasma markers of coagulation, fibrinolysis and endothelial dysfunction in 21 obese (10.1±1.5 years, mean ± standard deviation) and 22 healthy weight children (9.9±1.6 years), classified by Body Mass Index (BMI). TF-PCA and factor VII coagulant activity (FVII:C), plasminogen activator inhibitor (PAI-1, SERPINE1) and soluble vascular cell adhesion molecule 1 (sVCAM1) were higher in obese children. BMI correlated positively with TF-PCA, FVII:C, and PAI-1. Childhood obesity is associated with a procoagulant state and endothelial dysfunction. Studies are needed to assess whether weight reduction reverses these abnormalities.